Improving Letter Recognition Skills Through The Singing Method Assisted By Animation Media - Husnul Awaliyah; Muhammad Zaid; Ruri Muhammad P D (Indonesian Journal of Educational Technology, 2026)
This study aimed to improve first-grade students' letter recognition ability through the singing method assisted by animation media at SDN 14 Bontotene. This classroom action research was conducted in two cycles involving 33 students. Data were collected using observation sheets, letter recognition tests, and documentation, and were analyzed descriptively through teacher activity observations, student activity observations, and learning mastery data. The results showed that the animation-assisted singing method improved students' letter recognition ability. In cycle I, 8 students (24%) reached the mastery category, while 25 students (76%) had not yet reached mastery. In cycle II, 25 students (76%) reached mastery and 8 students (24%) had not yet reached mastery. Student activity increased from 58%, 75%, 83%, and 92% in cycle I meetings to 83%, 92%, 100%, and 100% in cycle II. Teacher activity also improved from 88%, 94%, 94%, and 100% in cycle I to 94%, 100%, 100%, and 100% in cycle II. These findings indicate that the singing method supported by animation media can make letter recognition learning more active, enjoyable, and effective for early-grade elementary students.